Religion and Religiousness of Poles in Observations of French Travellers in the Polish-Lithuanian Commonwealth in the 17th Century - Michalczuk, Agnieszka (Poznańskie Studia Slawistyczne, 2016)
In the 17th century, the Polish-Lithuanian Commonwealth became a country that French people liked to visit. Many of them left descriptions of the country which was different to their own in certain aspects. One of these aspects was Polish people’s religiousness and their attitude to nonCatholic religions. They were surprised at tolerance for people of another faith among the nobility and at the royal court, the co-existence of churches of different denominations and the lack of mutual aggression. On the other hand, they could see Polish people’s attachment to tradition and their original rites, at the same time pointing out their excessive demonstration of religious feelings, sometimes even bordering sanctimoniousness.